Authorship patterns in Computer Science Research in the Philippines - Pabico, Jaderick P. (Philippine computing journal)
We studied the pattern of authorship in computer science (CS) research in the Philippines using data mining and graph theory techniques on archives of scientific papers presented in the Philippine Computer Science Congresses from 2000 to 2010 involving 326 papers written by 605 authors...